(untitled) (Journal of Hama University, 2022)
The current study aimed at recognizing the skills of creative reading available in Arabic language book for fifth grade of basic learning, and at measuring the level of pupils’ mastery. The research used analytic descriptive approach. The researcher prepared a questionnaire of content analysis and a test to measure the skills of creative reading. He analyzed the content of the book titled ’Arabic is my language’ for fifth grade in the first semester of academic year 2020- 2021. The test was applied on a random sample of 35 pupils. The results of the content analysis showed that creative reading skills were distributed unevenly, so reading fluency skills were more available than other skills with a clear difference between them. Flexibility and originality skills were equal in their sub-skills with different percentages of availability, while the skill of expansion came in the last place. With regard to the level of pupils’ mastery of these skills, the test results showed that most pupils had mastery of creative reading skills from the middle level in the test skills as a whole. The same results apply for the skills of fluency and originality. As for the skill of flexibility, a decline appeared in the medium level at the expense of an increase in the low level. With regard to the expansion skill, the medium level came in the first place, with an increase in the low level. The results in its entirety are due to the fact that the pupils did not receive adequate training in these skills despite their abundance in their textbooks. The teacher way in dealing with these skills reduces their effectiveness on pupils. Some teachers may find it difficult to measure these skills, so they ignore them while evaluating their pupils